ULTIMATE BOUNDS OF RAPIDLY TIME-VARYING SYSTEMS: AN AVERAGING APPROACH - Kim Ngan, Dinh (HNUE Journal of Science: Journal of Natural Sciences, 2025)
This paper addresses the problem of state bounding for rapidly time-varying linear systems with bounded disturbances. Based on an averaging method and Lyapunov scheme, we derive an explicit bound on the time-scale parameter for which an explicit form of asymptotic bound of solutions is obtained. An application in fast switching systems is presented to illustrate the effectiveness of the analysis results.